WORK ACCIDENTS WITH BIOLOGICAL MATERIAL: ANALYSIS OF THEIR OCCURRENCE AND RECORDING - Grassyelly Silva Gusmão; Adriana Cristina de Oliveira; Camila Sarmento Gama (Universidade Federal do Paraná, 2013)
This epidemiological study was undertaken in a philanthropic hospital in Minas Gerais, in May 2010, through the administration of a semi-structured questionnaire and consecutive analysis of the files of the Notifiable Conditions/Incidents Information System and the Notification of Occupational Accidents System. The aim was to determine the prevalence of occupational accidents involving biological material among the nursing team, and to compare the results with the records in the Notifiable Conditions Information System and Notification of Occupational Accidents, as well as to identify their characteristics. 17 (53.1%) accidents were reported involving biological material, 10 (31.2%) recorded in the Notifiable Conditions Information System and 5 (15.6%) in the Notification of Occupational Accidents System. Venepuncture and the inadequate disposal of material were associated with 52.9% and 47.1% of the accidents, respectively. The difference between the notification of the accident on the different systems can express ignorance of its flow and legal importance, and of the worker's rights.